EFFECT OF EPIPHYTES EXTRACT ON THE PEROXIDASE ACTIVITY IN THE CROP SEEDLINGS CHALLENGED WITH FUNGAL PATHOGENS - HAMZAH JUMAH ESSA BARKAH; LOKESH S (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the present study to test the angiospermic epiphytes such as Bulbophyllum propinquum and Dendrophthoe falcata for their effect against some pathogenic fungi of sorghum, paddy and chilli, through seed treatment and foliar spray in challenging with the infectivity of the pathogens. Methods: The plant extracts were carried out by the Soxhlet extraction method and culture of pathogenic fungi were cultured and maintained in vitro for further use. The peroxidase (POX) enzyme activity in the seedlings was measured spectrophotometrically at 300 nm and expressed as Δ optical density 300 nm/min/mg protein. Results: The results of this study indicated 92 and 98% seed germination in the control samples, respectively. In the chilli and paddy which were reduced to 64 and 58% in seedlings inoculated with Colletotrichum dematium, Drechslera oryzae, correspondingly. Similar observation was made in sorghum samples on treatment with Fusarium solani and Fusarium oxysporum, whose germination was drastically reduced to 74 and 69% compared to control (92%). In all the cases, seed treated with epiphytes extracts indicated the stimulated germination over pathogen inoculated samples. In parallel to this, the peroxidase assay also indicated its diminished/reduced activity in pathogen treated seedlings of the selected crop species. Seedlings of epiphytes extract treatment challenged with respective pathogens showed an increased activity over only pathogen treated samples. Conclusion: The results clearly indicated the influence of POX in early growing stages of the seedlings corresponds to 12–72 h of incubation in spite of pathogenic activity. Thus, it proved the loss of enzyme activity seedlings on pathogen infection. Contrastingly, POX activity in the seedlings irrespective of the crop species remained high during the early growth stages of the seedlings.